2014
DOI: 10.1111/jvp.12134
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic evaluation of marbofloxacin in the treatment of Haemophilus parasuis and Actinobacillus pleuropneumoniae infections in nursery and fattener pigs using Monte Carlo simulations

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Vilalta, C., Giboin, H., Schneider, M., El Garch, F., Fraile, L. Pharmacokinetic/ pharmacodynamic evaluation of marbofloxacin in the treatment of Haemophilus parasuis and Actinobacillus pleuropneumoniae infections in nursery and fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 35 publications
(64 reference statements)
0
28
0
Order By: Relevance
“…MIC) within populations of microorganism may influence efficacy and the potential for resistance development in the target pathogen. Simulations of this variability in PK-PD have been used to evaluate marbofloxacin in the treatment of APP infections in nursery and fattening pigs, and showed that a single dose of 8 mg/kg would provide robust efficacy and minimise resistance development in APP with MICs of 0.03–0.12 μg/mL [9, 10] which are comparable to the APP MIC range reported here.…”
Section: Discussionmentioning
confidence: 67%
“…MIC) within populations of microorganism may influence efficacy and the potential for resistance development in the target pathogen. Simulations of this variability in PK-PD have been used to evaluate marbofloxacin in the treatment of APP infections in nursery and fattening pigs, and showed that a single dose of 8 mg/kg would provide robust efficacy and minimise resistance development in APP with MICs of 0.03–0.12 μg/mL [9, 10] which are comparable to the APP MIC range reported here.…”
Section: Discussionmentioning
confidence: 67%
“…These data should be analysed alongside antimicrobial pharmacokinetic data, which can be variable from one animal to another. Vilalta and others (2014) calculated, from a Monte Carlo simulation, the probability of PKPD target attainment taking into account the variability of drug exposure in pigs and the variability of MICs from respiratory bacterial isolates. This study also reported the cumulative fractions of response for several dosing schemes, meaning the proportion of animals in the population achieving a PKPD threshold values taking into account both the MIC distribution against the bacteria and the PK parameter distribution in the population.…”
Section: Discussionmentioning
confidence: 99%
“…[2]. Its properties of rapid absorption, good distribution, and broad spectrum against most of the swine respiratory pathogens, such as Haemophilus parasuis and Actinobacillus pleuropneumoniae , make it a good candidate to deal with a respiratory outbreak caused by any of these pathogens [3]. A. pleuropneumoniae is the causative agent of porcine pleuropneumonia, a worldwide disease with occasional clinical outbreaks that can have a severe economic impact [4].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics of marbofloxacin have been investigated in different animals and it demonstrated an almost 100% bioavailability, higher concentration in plasma and peripheral tissues in goats [17], cows [18], cats [19], sheep [20], dogs [21], and pigs [22, 23]. Although, some studies have been published on the pharmacokinetics of marbofloxacin in animals including pigs [3, 1822, 24, 25], yet the pharmacokinetic data of marbofloxacin in pig tissues and plasma is not sufficient enough to predict the efficacy of this drug precisely. Furthermore, the integration of pharmacokinetic (PK) data with pharmacodynamic (PD) data helps to establish the PK/PD indices (AUC/MIC, C max /MIC, T > MIC, AUC > MIC, etc.,) which are fundamental to predict efficacy and minimize resistance development [26, 27].…”
Section: Introductionmentioning
confidence: 99%